1985
DOI: 10.1104/pp.77.4.930
|View full text |Cite
|
Sign up to set email alerts
|

Controls on 22Na+ Influx in Corn Roots

Abstract: We have investipted the effects of hyperpolarization and depolariza-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
(27 reference statements)
2
20
0
1
Order By: Relevance
“…3) is in agreement with other findings (10,15,20,26,27). This does not necessarily contradict the findings of Kent and Lauchli (18), who found that the tissue concentrations of Na in cotton seedlings were unaffected by external Ca2`concentrations at 200 mM NaCl.…”
Section: Methodssupporting
confidence: 83%
“…3) is in agreement with other findings (10,15,20,26,27). This does not necessarily contradict the findings of Kent and Lauchli (18), who found that the tissue concentrations of Na in cotton seedlings were unaffected by external Ca2`concentrations at 200 mM NaCl.…”
Section: Methodssupporting
confidence: 83%
“…It has long been known that transfer of root tissues of many plant species to cation uptake solutions without calcium causes rapid changes in ion uptake patterns, presumably as a result of membrane destabilization (7,12). Rates of sodium influx were considerably increased within 30 min of transfer of maize root segments to solutions without an external source of calcium (Table I).…”
Section: \5%mentioning
confidence: 84%
“…Segments were incubated for 30 min been invoked to explain concentration dependent influx kiix of sodium expressed as a percentage of control rates with netics (7,12). Thus, the percent inhibition of sodium uptake mm calcium concentration in the uptake solution (100%).…”
Section: \5%mentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in cation influx by the addition of Ca 2ϩ ions is also important to the postulate that this transporter may play a role in the uptake of Na ϩ and in plant response to salinity. At the whole plant level it has been shown that the addition of Ca 2ϩ ameliorates Na ϩ toxicity (38), reduces Na ϩ uptake and inhibits translocation (39,40). At the cellular level it was recently shown that Ca 2ϩ partially abolishes the uptake of Na ϩ into wheat root cells through nonselective cation channels (41).…”
Section: Discussionmentioning
confidence: 99%